Barriers to effective communication in UAE community pharmacies: general public perspectives on enhancing patient-pharmacist interaction and policy development - Zelal Kharaba; Ahmad Al-Azayzih; Sayer Al-Azzam; Anan Jarab; Hisham E. Hasan; Dania Rahhal; Feras Jirjees; Khalid A. Al-Kubaisi; Monia H. Aljumah; Faris El-Dahiyat; Sara Meer; Mohammad A. Y. Alqudah; et al. (Journal of Pharmaceutical Policy and Practice)
Background Community pharmacies serve as accessible points of care, offering essential services such as medication dispensing, health consultations, vaccinations, and chronic disease management, thereby playing a critical role in the healthcare system. This study aims to identify and evaluate the factors that obstruct general public-pharmacist interactions, providing insights to enhance pharmacy environments.Methods A total of 406 general publics were surveyed using a validated questionnaire. Statistical analysis was performed with categorical variables presented as frequencies and percentages, and continuous variables as medians with 95% confidence intervals. Binary regression models were used to explore the relationships between sociodemographic characteristics and communication barriers, with a significance level set at p < 0.05 for all analyses.Results The primary reasons for pharmacy visits were collecting prescription medications (61.58%) and purchasing OTC products (55.17%), while health screenings were less common (9.11%). Barriers to effective communication included crowded environments (61.58%), limited counseling time (45.81%), and lack of privacy (45.07%). Binary logistic regression revealed that participants who visited the pharmacy weekly were 5.5 times more likely to experience high environmental barriers (OR: 5.502, p = 0.002), while interacting with younger pharmacists increased the likelihood of personal barriers (OR: 12.357, p = 0.025). Pharmacy proximity (75.12%) and shorter waiting times (47.29%) were the most influential factors in pharmacy preference, while additional services had minimal impact (20.2%).Conclusion Effective communication is crucial in community pharmacies for high-quality healthcare. This study identifies key barriers in the UAE and offers insights into targeted interventions to improve communication and public satisfaction.